ANALISIS SISTEM PERENCANAAN DAN PENGADAAN ANGGARAN DINAS ENERGI DAN SUMBER DAYA MINERAL - Dwi Indah Permata (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
Office Stationery is a very influential support in carrying out operational activities every day. All work activities require the availability of adequate stationery. By fulfilling the needs of Office Stationery, work activities can run optimally. Planning is a very crucial stage in a management function, most importantly in experiencing a changing external environment moving forward. Planning should be more rational, systematic and not based on intuition and hunches. Procurement in the field of Office Stationery providers must meet the needs so that there is no waste of cash. In the implementation of the Procurement of goods / services in a government agency is a matter that is closely related to using the rules of the APBN or APBD. Therefore, the management of stationery must receive specific attention by managing every expenditure of goods to be used. The purpose of this research is to find out the Planning and Procurement System of the Office Stationery Budget in the Mineral Resources Energy Service.